Aortic Coarctation in Neonates and Infants: Balloon Angioplasty or Surgical treatment? - Y. Truba; I. Dytkivski; E. Imanov; O. Plyska; L. Moshkyvska; I. Dzuriy; O. Golovenko; V. Lazoryshynetz (Ukrainian Journal of Cardiovascular Surgery, 2019)
Coarctation of the aorta (CoA) is a discrete stenosis of the proximal thoracic aorta. The common clinical pattern is congestive heart failure in infancy. Treatment methods include balloon angioplasty (BA) and surgical repair in this age group. Percutaneous balloon angioplasty is a less invasive method for the repair of discrete coarctation but remains controversial as a primary treatment strategy for a native coarctation. This study aimed at comparing the efficacy and outcome of balloon angioplasty and surgical repair in infants with aortic coarctation younger than one year old.Methods. Between January 2007 and December 2018, 155 patients with native aortic coarctation were treated in M.M. Amosov National Institute of Cardiovascular Surgery. This retrospective study evaluated the results of the two methods in patients younger than one year old with the diagnosis of aortic coarctation. Group 1 included 78 patients following balloon dilatation for discrete coarctation. Group 2 included 77 patients following surgical resection with end-to-end anastomosis. Patients with complex cardiac anomalies were not included in this study.Results. Immediate results revealed no significant difference in the efficacy of the two methods (p=0.17), with the rate of recurrent coarctation significantly lower in the surgery group [3 (3.8%) vs. 32 (41%), p<0.05]. The mean hospital stay was 6.7±3.2 days in the balloon angioplasty group and 21.4±8.1 days in the surgery group, which constitutes a significant statistical difference (p<0.05). Aneurysm formation was not reported.Conclusion. Our own experience testifies that both surgical correction and balloon angioplasty of aortic coarctation in infants are effective and give a good immediate result. Balloon angioplasty may be an acceptable alternative to surgical treatment in infants with critical aortic coarctation, although it is accompanied with an increased level of re-coarctation. Recoarctation after balloon dilatation is manifested in the first 3-4 months of postoperative follow-up and requires repeated correction by a surgical or endovascular method.